Financial and occupational impact of low anterior resection syndrome in rectal cancer survivors. (14th April 2021) - Garfinkle, Richard; Ky, Aurelie; Singh, Aashiyan; Morin, Nancy; Ghitulescu, Gabriela; Faria, Julio; Vasilevsky, Carol‐Ann; Boutros, Marylise
Abstract: Aim: The aim of this study was to assess bowel‐related financial stress and strain and to evaluate its association with global quality of life. Method: This was a retrospective cohort study with cross‐sectional follow‐up including consecutive patients who underwent restorative proctectomy for neoplastic disease of the rectum at a single university‐affiliated hospital in Montreal, Quebec, Canada. Bowel‐related financial impact and occupational impact were compared between patients with major low anterior resection syndrome (LARS) and those with minor/no LARS. The association between LARS, bowel‐related financial impact and global quality of life (QoL) was then assessed in a multiple logistic regression model. Results: Of 180 eligible rectal cancer survivors who were contacted, 154 completed the questionnaires (response rate 47.1%) at a median follow‐up of 57.5 months (interquartile range 34.1–98.1) after proctectomy. Individuals with major LARS reported a higher prevalence of bowel‐related financial stress (53.2% vs 5.6%, p  < 0.001) and strain (42.2% vs 5.6%, p  < 0.001) compared with those with minor/no LARS. Among those who were working preoperatively ( n  = 100), the majority of participants with major LARS reported an impact of their new bowel function on their ability to work (70.6%), including delayed return to work (44.1%), the need to change schedules (35.3%) or roles (20.6%), and complete long‐term medical absence from work (14.7%). On multiple logistic regression, major LARS with financial impact (OR 4.50, 95% CI 1.57–13.77) was associated with low global QoL compared with minor/no LARS. Conclusion: Major LARS was associated with considerable financial stress and strain and difficulties in returning to work.